Dextransucrase Expression Is Concomitant with that of Replication and Maintenance Functions of the pMN1 Plasmid in Lactobacillus sakei MN1 - Nácher-Vázquez, Montserrat; Ruiz-Masó, José A.; Mohedano, María L.; del Solar, Gloria; Aznar, Rosa; López, Paloma (Frontiers in Microbiology, 2017)
The exopolysaccharide synthesized by Lactobacillus sakei MN1 is a dextran with antiviral and immunomodulatory properties of potential utility in aquaculture. In this work we have investigated the genetic basis of dextran production by this bacterium. Southern blot hybridization experiments demonstrated the plasmidic location of the dsrLS gene, which encodes the dextransucrase involved in dextran synthesis. DNA sequencing of the 11,126 kbp plasmid (pMN1) revealed that it belongs to a family which replicates by the theta mechanism, whose prototype is pUCL287. The plasmid comprises the origin of replication repA, repB and dsrLS genes, as well as seven open reading frames of uncharacterized function. Lb. sakei MN1 produces dextran when sucrose, but not glucose, is present in the growth medium. Therefore, plasmid copy number and stability, as well as dsrLS expression, were investigated in cultures grown in the presence of either sucrose or glucose. The results revealed that pMN1 is a stable low-copy-number plasmid in both conditions. Gene expression studies showed that dsrLS is constitutively expressed, irrespective of the carbon source present in the medium. Moreover, dsrLS is expressed from a monocistronic transcript as well as from a polycistronic repA-repB-orf1-dsrLS mRNA. To our knowledge, this is the first report of a plasmid-borne dextransucrase-encoding gene, as well as the first time that co-transcription of genes involved in plasmid maintenance and replication with a gene encoding an enzyme has been established.